Using FB to Investigae Teachers’ Strategies in Teaching English: A Case of Simeulue Alumni - Rahmat Junaidi (English Education Journal, 2018)
This study is conducted to explore students’ perception and their suggestions on teachers’ teaching strategies in teaching English. In so doing, a qualitative research design was employed and 19 Students were purposively selected. Those respondents are current university students who are studying at various universities in Banda Aceh. To gather the respondents’ perspective, Facebook (FB) group chat was used as a  means  to  describe  their  past  experiences  in  learning  English.  Their gathered responses have been processed in accordance with thematic analysis procedures. The findings of this study revealed that Senior High School teachers in Simeulue have used particular strategies in teaching English. It was indicated that using textbook, engaging in sentence formula and word memorization, doing sentence translation, repeating words after teacher, reading aloud, and working the task in pairs and groups  are  among  the  most  commonly  utilized  strategies  as  perceived  by  the respondents. In response to teachers’ teaching strategies, the majority respondents recommended a new model in their teachers’ teaching strategies; which are a shift to communicative  teaching  strategy  incorporating  media  and  ICTs  based  language teaching. Hence, it is recommended that the senior high school teachers pinpoint the use of integrated teaching technique employing technology in their school.